2011
DOI: 10.3122/jabfm.2011.06.110094
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Cancer Screening Rates among Appalachian and Non-Appalachian Residents of Kentucky

Abstract: Background: Having diabetes may increase the odds of late-stage breast cancer. In Kentucky, the rates of late-stage disease are higher in rural than in urban areas, particularly in rural Appalachia. The objectives of the study were to examine the relationship between diabetes and cancer screening and to determine whether Appalachia residence modifies this association.Methods: One thousand thirty Kentucky adults responded to a 2008 telephone survey that measured whether they had diabetes; lived in Appalachia; h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 27 publications
1
28
1
Order By: Relevance
“…Screening in accordance with guidelines has been estimated at 49% in Appalachian Ohio (37), which has among the lowest rates of uninsured in Appalachia (22). Fleming and colleagues found that among Kentucky residents, those living in Appalachia were half as likely as non-Appalachians to report endoscopy screening for colorectal cancer in the past 10 years (38). While colorectal cancer screening rates for the Mississippi Delta are not available, breast cancer screening has been shown to be lower there than in the rest of the United States (39).…”
Section: Discussionmentioning
confidence: 99%
“…Screening in accordance with guidelines has been estimated at 49% in Appalachian Ohio (37), which has among the lowest rates of uninsured in Appalachia (22). Fleming and colleagues found that among Kentucky residents, those living in Appalachia were half as likely as non-Appalachians to report endoscopy screening for colorectal cancer in the past 10 years (38). While colorectal cancer screening rates for the Mississippi Delta are not available, breast cancer screening has been shown to be lower there than in the rest of the United States (39).…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have assessed CRC screening patterns among Appalachian populations and many of these studies have documented lower CRC screening rates, with reported rates as low as 32% [24, 25, 2729, 32]. Since CRC screening rates are low and there is an increase in CRC mortality rates among residents of Appalachia Ohio, innovative strategies are needed to increase CRC screening rates.…”
Section: Introductionmentioning
confidence: 99%
“…11 Women with diabetes had lower rates of mammography screening, though not of clinical breast examination. The differences in screening rates were approximately 10% to 15%.…”
Section: Cancer Screening and Follow-upmentioning
confidence: 99%